STRATEGI GURU DALAM MEMOTIVASI BERPIKIR KRITIS PADA ANAK USIA DINI DI TK KOTA SAMARINDA - Azizah, Noor; Robingatin, Robingatin; Kusasi, Kusasi (Universitas Muhammadiyah Ponorogo, 2023)
This research is motivated by the current education system, which tends to emphasize that critical thinking is only developed and taught at higher levels of education but less so in early childhood. Therefore, it is important to instill and motivate critical thinking skills from an early age. This research aims to: (1) describe the development of critical thinking in early childhood in Samarinda; (2) describe the strategies used by kindergarten teachers to motivate critical thinking in early childhood in Samarinda; and (3) describe the supporting and inhibiting factors in motivating critical thinking in early childhood. This research investigates the strategies used by kindergarten teachers in Samarinda to motivate critical thinking in early childhood, specifically at three schools: Islamic Center Kindergarten, Ittihad Kindergarten, and Fastabiqul Khairat Kindergarten. This research is a qualitative descriptive study that uses data collection techniques such as observation, interviews, and documentation. Data analysis techniques include data condensation, data presentation, conclusion drawing and verification, and data validity testing using data triangulation. The results of this research are as follows: (1) In the development of critical thinking, children were found to have a strong sense of curiosity, often ask deep questions, can analyze information, are willing to explore ideas, actively participate in learning, and can solve problems independently. Teacher strategies to motivate critical thinking in young children demonstrate a variety of approaches to stimulating critical thinking. Each strategy has its own unique benefits. Educators have a variety of tools and techniques that they can use to stimulate critical thinking in children. Combining diverse strategies can provide a richer and deeper learning experience. Supporting factors in motivating critical thinking in children include parental support, collaboration with other teachers, adequate resources, good communication between mothers and children, the use of creative teaching strategies, and positive encouragement. However, there are also inhibiting factors that need to be considered, such as time constraints, lack of training in teaching critical thinking, excessive academic pressure, miscommunication with parents, and constraints in the learning environment.